Obravnava skladnje pri pouku slovenščine v tretjem triletju osnovne šole, v gimnaziji ter srednjem strokovnem in poklicnem izobraževanju - Smolej, Mojca (Slavia Centralis, 2018)
The article presents a shortened and simplified overview of the results of the analysis regarding teaching Slovene syntax in elementary and secondary school. A review of printed learning material showed that most autonomous workbooks for teaching Slovene do not encourage elementary and high school pupils to reflect on the importance of the acquired knowledge in the field of syntax. In the examined autonomous workbooks, it is hardly possible to detect critical reflection and understanding of acquired knowledge.
Keywords: gimnazija; osnovna šola; pouk slovenščine; primary school; skladnja; Slovene; slovenščina; srednje strokovno in poklicno izobraževanje; syntax